Exploring the rise and diversity of health and societal issues that use a public health approach: A scoping review and narrative synthesis. - Alison Hurst; Nick Shaw; Daniele Carrieri; Ken Stein; Katrina Wyatt (PLOS Global Public Health)
There is an increase in calls across diverse issues for a "public health approach" however, it is not clear whether there is any shared understanding in approach in its conceptualisation or implementation. Our aims were to (1) identify and categorise the issues which discuss a public health approach within published literature since 2010, (2) chart the descriptions and applications of public health approaches across and within four purposively sampled categories of issues, and (3) capture any evaluations conducted. A scoping review of published literature was undertaken; Seven leading databases were searched: AMED, APA PsycInfo, ASSIA, CINAHL complete, Cochrane Library (Review), Embase, and MEDLINE for articles published between 2010 and 2022 which have applied, described or called for a "public health approach" to address any issue. 3,573 studies were identified through our initial searches, of these 1,635 articles were recognised for possible inclusion from analysis of titles and abstract. The final number of included studies was 1,314. We identified 28 categories, 26 of which were societal issues, where a public health approach is being advocated. We purposively selected four of these categories; adverse childhood experiences; end of life care; gambling addiction and violence reduction/ knife crime for further analysis of the approach including how it was conceptualised and operationalised; less than 13% of the studies described the implementation of a public health approach and there was considerable heterogeneity across and within categories as to how this was done. Since 2010 there have been increasing calls for a public health approach to be taken to address health and societal challenges. However, the operationalisation of a public health approach varied extensively and there were few evaluations of the approach. This has implications for policy makers and those involved in commissioning related approaches in the future as the evidence-base is limited.